An indoor air pollution research strategy for the United Arab Emirates - Jacqueline MacDonald Gibson; Rahaf Ajaj; Ahmed Al Khazraji; Latifa Al Shamsi; William P. Bahnfleth; Daniel Bonn; Katherine Bronstein; Rania Dghaim; Taher Eldanaf; Mohamed El Sadig; Moshood Olawale Fadeyi; Diana Francis; et al. (Indoor Environments)
Clean indoor air is vital for health in all settings, especially in locations where extreme climates restrict outdoor activity, such as in the United Arab Emirates (UAE). UAE summer temperatures routinely exceed 42°C (108°F), discouraging outdoor activity and limiting natural ventilation of structures. Yet, little research is available on indoor air quality in the UAE. To inform the design of a new indoor air quality program, the Abu Dhabi Public Health Centre commissioned a study to characterize and prioritize knowledge gaps on indoor air quality and its relationship to health in the UAE and to identify potential partners for the program. Research gaps and priorities were identified by a panel of 16 international and local indoor air quality experts through a two-day structured, in-person workshop and follow-up survey. Key partners were identified through a stakeholder mapping exercise and e-mail survey of 79 government agencies and nongovernment organizations. The expert panel concluded that the most important short-term research need is to characterize the major sources of indoor air pollution and the most frequently occurring pollutants. The panel recommended establishing a national indoor air quality observatory encompassing a wide range of settings, including residences, schools, mosques, healthcare facilities, shopping malls, and other public spaces. Indoor air quality monitors would be permanently placed to establish baseline indoor air quality, provide data to estimate source contributions, and enable tracking of changes over time. The stakeholder mapping exercise identified ten agencies that should be involved in planning, including the Abu Dhabi Public Health Centre, Department of Health–Abu Dhabi, Environment Agency–Abu Dhabi, Abu Dhabi Department of Energy, and Emirates Public Health Association. While focused on the UAE, the methods and research priorities in this study may be useful for planning indoor air quality improvement campaigns in other high-income nations.